Implementasi Program Keadabiahan dalam Membentuk Karakter Religius pada Peserta Didik di SMP Adabiah Padang - Munthe, Desi Ramadani; Kanus, Oktari (TSAQOFAH, 2025)
This study aims to describe the implementation of the keadabiahan program in shaping the religious character of students at SMP Adabiah Padang. Religious character is a crucial aspect of character education, particularly in schools that are not explicitly based on Islamic values. The keadabiahan program is designed as a strategy for developing students’ personalities to be noble in character, disciplined, and highly aware of religious obligations. This research employs a qualitative field study approach, with data collected through observation, in-depth interviews with the principal, teachers, and students, and documentation of the implemented keadabiahan programs. Data analysis was conducted descriptively through stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of the keadabiahan program is carried out through routine activities such as habituation of congregational prayer, maintaining etiquette in communication and behavior both inside and outside the classroom, environmental manners, and manners during eating and drinking. The program is supported by a religious school environment and active participation from the entire school community. Findings indicate that the program significantly contributes to shaping students’ religious character, as evidenced by increased worship discipline, politeness, and social awareness. Thus, the keadabiahan program at SMP Adabiah Padang can serve as an effective model for religious character development and can be replicated in other schools with similar visions.